PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA MI - Fithriyah, Dewi Niswatul; Mashari (JEMI, 2025)
Learning that emphasizes critical thinking skills is essential to equip students with the ability to analyze, evaluate, and solve problems. One approach that can foster these skills is the Problem Based Learning (PBL) model, which encourages students to actively search for solutions to real-world problems. This study aims to examine the impact of implementing the PBL model on the critical thinking skills of students in Madrasah Ibtidaiyah. The research question addressed is how the application of PBL can enhance students' critical thinking skills compared to conventional teaching methods. This research uses an experimental design with a pretest-posttest control group approach. The sample consists of two groups: an experimental group using the PBL model and a control group using conventional methods. Data was collected through pretest and posttest assessments of critical thinking skills. The results show that the experimental group experienced a significant improvement in critical thinking skills, with a higher posttest average score compared to the control group. Based on these results, it can be concluded that the PBL model is effective in enhancing the critical thinking skills of students in MI.